Phytoplankton response to a plume front in the northern South China Sea - Q. P. Li; Q. P. Li; W. Zhou; W. Zhou; Y. Chen; Y. Chen; Z. Wu (Biogeosciences, 2018)
Due to a strong river discharge during April–June 2016, a persistent salinity front, with freshwater flushing seaward on the surface but seawater moving landward at the bottom, was formed in the coastal waters west of the Pearl River estuary (PRE) over the northern South China Sea (NSCS) shelf. Hydrographic measurements revealed that the salinity front was influenced by both the river plume and coastal upwelling. On shipboard nutrient-enrichment experiments with size-fractionation chlorophyll a measurements were taken on both sides of the front as well as in the frontal zone to diagnose the spatial variations of phytoplankton physiology across the frontal system. We also assessed the size-fractionated responses of phytoplankton to the treatment of plume water at the frontal zone and the sea side of the front. The biological impact of vertical mixing or upwelling was further examined by the response of surface phytoplankton to the addition of local bottom water. Our results suggested that there was a large variation in phytoplankton physiology on the sea side of the front, driven by dynamic nutrient fluxes, although P limitation was prevailing on the shore side of the front and at the frontal zone. The spreading of plume water at the frontal zone would directly improve the growth of microphytoplankton, while nano- and picophytoplankton growths could have become saturated at high percentages of plume water. Also, the mixing of bottom water would stimulate the growth of surface phytoplankton on both sides of the front by altering the surface N∕P ratio to make it closer to the Redfield stoichiometry. In summary, phytoplankton growth and physiology could be profoundly influenced by the physical dynamics in the frontal system during the spring–summer of 2016.